ABILITIES AND FACTORS THAT AFFECT SCIENCE LITERACY OF ELEMENTARY SCHOOL STUDENTS IN WEST JAVA, INDONESIA - Widiyanto, Rohmat; Fauzan, Fauzan; Latip, Asep Ediana; Rizqa, Nur Luthfi; Suryaningsih, Tri; Uswatun, Din Azwar (JMIE (Journal of Madrasah Ibtidaiyah Education), 2025)
The issue of science literacy, which was published at the end of 2022 by PISA, is an important topic in Indonesia, which includes aspects of context, competence and knowledge. This study aims to analyze the science literacy ability of final grade 5 students in Depok, West Java which includes aspects of context, competence and knowledge. In addition, this study was conducted to investigate factors that can affect the science literacy ability of elementary school students in Depok, West Java. The type of research conducted is quantitative descriptive. The number of samples in this study was 123 samples from grade 5 in Depok, West Java. The sample collection technique uses the purposive sampling technique. Data on students' science literacy abilities is obtained from test results in the form of science literacy test sheets based on the PISA question standards. The data analysis technique uses quantitative descriptive analysis techniques. The results of the study showed that the average science literacy ability of 5th grade students in Depok, West Java was included in the medium category with a percentage of 59.57%. If described in each science literacy domain, the science literacy ability in the context aspect was 59.03% with the medium category, the science literacy ability in the knowledge aspect was 58.96% with the low category, and the science literacy ability in the competency aspect was 57.82% with the low category.